An outlook on larval morphology of Copelatinae diving beetles with phylogenetic considerations (Coleoptera: Adephaga, Dytiscidae) - Alarie, Yves; Michat, Mariano C.; Watanabe, Kohei; Shaverdo, Helena; Wang, Liang-Jong; Watts, Chris H. S. (Zootaxa, 2022)
The larvae of 12 species of Copelatinae, Copelatus alternatus Sharp, 1882, C. caelatipennis princeps Young, 1963, C. glyphicus (Say, 1823), C. japonicus Sharp, 1884, C. masculinus Régimbart, 1899, C. nakamurai Guéorguiev, 1970, C. oblitus Sharp, 1882, C. parallelus Zimmermann, 1920, C. tenebrosus Régimbart, 1880, Exocelina australiae (Clark, 1863), E. ferruginea (Sharp, 1882), and Liopterus haemorrhoidalis (Fabricius, 1787) are described or redescribed, including for the first time a detailed chaetotaxy analysis of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. A provisional parsimony analysis based on larval characteristics of 13 copelatine species was conducted using the program TNT, which reinforces the monophyletic origin of the Copelatinae. Copelatinae larvae stand out from the remaining Dytiscidae based on several synapomorphies, including the unusual shorter length of the mesothoracic legs. Legs and urogomphi morphology suggest that Copelatinae larvae studied evolved a creeping way of life. The provisional phylogenetic analysis presented in this study provides some arguments for the validity of the taxonomic status of the genera Liopterus Dejean, 1833 and Exocelina Broun, 1886.